Look before you leap: A case series of conidiobolomycosis from the Indian subcontinent - Nitin Gupta; Rajeev Kumar; Prashant Ramteke; Manish Soneja (Journal of Family Medicine and Primary Care, 2018)
Conidiobolomycosis is an extremely rare subcutaneous rhinofacial indolent infection caused by Conidiobolus coronatus and Conidiobolus incongruus. It is reported mainly from the tropical and subtropical parts of the world, mostly in form of isolated case reports or small case series. Two immunocompetent male patients presented to our center with indolent nasal swelling and features of nasal obstruction. They were treated outside with antibiotics and/or steroids and were referred to us with nonresolving symptoms. Both of them were diagnosed based on the characteristic histopathological findings and were successfully treated with saturated solution of potassium iodide. Conidiobolomycosis is an important differential in patients presenting with centrofacial swelling. Early suspicion and timely referral by the primary care physicians will help in early diagnosis and treatment of this disease.